1458 Compliance of Abdominal X-ray Requesting with iRefer Guidelines in CDDFT. (12th October 2021) - McGurk, R; Ross, E; Toward, M
Abstract: Aim: 100% of Abdominal x-ray (AXR) requests in the trust should be compliant with iRefer guidelines. Therefore, with this audit we hope to evaluate the compliance of our hospitals with said guidelines. Method: This audit was retrospective with AXRs taken between 23 – 29 th of November 2020 being analysed for compliance creating our first loop. On the 1 st of December we placed our intervention. This came in the form of educational posters in the four areas that request the majority of AXRs. Following this, a further weeks' worth of AXRs were assessed for compliance between 2 nd – 8 th of December 2020. Results: Between 23-29/11/20 there were 67 AXRs requested. Eight of these were excluded according to our exclusion criteria, leaving a total of 59 AXRs to be assessed. After reviewing the request cards for these AXRs, 17 were non-compliant (28.8%). Following the intervention, AXR requests were re-audited. Between 2-8/12/20 there were 69 AXRs requested. Six were excluded leaving a total of 63 AXRs to be assessed. After review, 22 were non-compliant (34.9%) Conclusions: In both loops of this audit, the standard of 100% compliance with iRefer guidelines was not met. There was a high percentage of non-compliance in both loops with a rate of 28.8% and 34.9% respectively – a decrease in compliance. One possible reason to account for this was due the changeover of Junior Doctors within the trust on 2/12/20. Our interventional posters were placed in only half of the Trusts hospitals which may also account for the decrease in compliance.